Ecological impact of mining brownfields in Bucovina (Romania) - Viorel CHIRIȚĂ; Daniela MATEI (Georeview, 2022)
The decline of mining activities in Romania has led to the appearance of large areas of mining waste, buildings and decommissioned equipment. Known by the name of mining wastelands, they challenge both the environment as well as the communities in which they are located. The problems created by the mining wastelands generate shock waves in the development of the rural territories hosting them and block their sustainable development. This paper highlights the stages of the evolution of different types of mining wastelands in Bukovina, with an emphasis on the environmental component, as well as on their possible integration using various forms of valorization. The data was gathered in 2017 as part of a research called “La dynamique des paysages culturels intégrant des aires avec des friches minières. Rétrospectives et perspectives géographique en Bucovine (Roumanie) et en Wallonie (Belgique)”, funded by “L`Agence Universitaire de la Francophonie”. We used the Rapid Impact Assessment Matrix (RIAM) methodology to assess the environmental impact of mining wastelands, which included 5 evaluation criteria and 15 components investigated (6 physical-geographical and ecological components, plus 9 socio-economic and cultural ones). The findings indicate that the ecological impact of abandoned mining areas is directly related to the area they occupy as well as the morphoclimatic system in which they are located. The socioeconomic component analysis highlighted the role of mine closure in increasing unemployment and lowering living standards, as well as a community takeover of some infrastructure elements through direct involvement of local government.